Internacionalizace společnosti EPRIN, spol. s r. o. na slovenský trh - Bártek, Ondřej (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Tato diplomová práce je zaměřena na možné formy internacionalizace. Cílem práce je navržení možné strategie internacionalizace společnosti EPRIN, spol. s r. o. na slovenský trh. Teoretická východiska se zabývají vysvětlením jednotlivých přístupů k internacionalizaci a také možnými formami vstupu na zahraniční trh. Na teoretická východiska navazuje analýza současného stavu, kde je popsána společnost, jsou provedeny jednotlivé analýzy a je shrnuta její konkurenceschopnost. Na základě zjištění je navrhnuta možná strategie vstupu na zahraniční trh, která by měla přinést nové zákazníky, pomoci se zviditelnit a přiblížit se dalším trhům

This diploma thesis is focused on the possible forms of internationalization. The aim is to propose possible strategies of internationalization of EPRIN, spol. s r. o. company on Slovak market. Theoretical resources deal with the explanation of different approaches to internationalization and possible forms of entry into foreign markets. After the theoretical resources follow analysis of the current state, where company is described, are made analyses and is summarized its competitiveness. On the base of finding is suggested a possible strategy to reach foreign market, which should bring new customers, to help raise the profile and reach out to other markets.
Internationalization of Company EPRIN, spol. s r. o. on Slovak Market
Keywords: Internacionalizace; společnost EPRIN; spol. s r. o.; Slovensko; dceřiná společnost; strategie; Internationalization; company EPRIN; spol. s r. o.; Slovakia; subsidiary company; strategy